GovTech for Georgia : A Whole of Government Approach as a Key Foundation for the Digital Economy in Georgia - World Bank (World Bank, Washington, DC, 2021)
This note presents main findings of the GovTech Snapshot Assessment for Georgia, forming part of a larger World Bank global engagement on GovTech and Advisory Services and Analytics (ASA) in the South Caucasus on Transforming Government Services through Digital Innovations. The objective of the note is to conduct an initial GovTech stock-taking, using the GovTech conceptual framework within the broader Digital Economy context. Starting with a first analytical phase in 2021 and to be continued through a second phase of implementation support in 2022, the assessment focuses on key thematic areas in line with client interest to help identify entry-points and reform options. It applies a simplified and customized version of the Digital Government Readiness Assessment Methodology (DGRA), assessing key thematic dimensions and developing a menu of reform options in line with client priorities.